Moderasi Beragama dan Konstruksi Identitas Berbasis Lokalitas: Studi Pada Komunitas Hindu dan Islam di Makam Medana dan Pura Medana Lombok Utara - I Gusti Agung Dharmawan (Jayapangus Press, 2025)
This study aims to explore the practice of religious moderation and the construction of identity among Hindu and Muslim communities in the sacred sites of Makam Medana and Pura Medana, North Lombok. The research focuses on socio-religious dynamics, moderation practices, and the formation of collective identity within a multireligious context. A descriptive qualitative approach was employed, with data collected through in-depth interviews, observations, and documentation. Data were analyzed using Miles and Huberman’s interactive model, consisting of data reduction, presentation, and verification. The findings reveal that the Medana community has successfully maintained interreligious harmony through customary mechanisms such as sangkep (traditional council meetings), the active roles of religious leaders, and joint participation in social activities. The construction of local identity is reflected in the shared respect for sacred sites—Makam Medana for Muslims and Pura Medana for Hindus—which serve as symbols of pluralism and cultural integration. Values of tolerance, cooperation, and respect for local traditions underpin social cohesion amid potential differences. Theoretically, this research contributes to the development of religious moderation studies grounded in local culture, while practically offering insights for strengthening social harmony through local wisdom–based approaches.